Amino acids regulate salinity-induced potassium efflux in barley root epidermis - Cuin, Tracey Ann; Shabala, Sergey (Planta, 2007)
The amino acid content increases substantially in salt-stressed plants. The physiological relevance of this phenomenon remains largely unknown. Using the MIFE ion flux measuring technique, we studied the effects of physiologically relevant concentrations of 26 amino acids on NaCl-induced K⁺ flux from barley root epidermis. We show that 21 (of 26) amino acids caused a significant mitigation of the NaCl-induced K⁺ efflux, while valine and ornithine substantially enhanced the detrimental effects of salinity on K⁺ homeostasis. Our results suggest that physiologically relevant concentrations of free amino acids might contribute to plant adaptive responses to salinity by regulating K⁺ transport across the plasma membrane, thus enabling maintenance of an optimal K⁺/Na⁺ ratio as opposed to being merely a symptom of plant damage by stress. Investigating the specific mechanisms of such amelioration remains a key issue for future studies.